2012
DOI: 10.1021/jp207385h
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Isolated Molybdenum(VI) and Molybdenum(IV) Oxide Species on Silica: Periodic and Cluster DFT Studies

Abstract: The structure of monomeric molybdenum oxide species on silica is still a subject under debate. In this work, a large number of advanced silica models are used to study molybdena−silica system with density functional theory. The calculated relative energies of the monooxo and dioxo Mo(VI) species depend on the location of the Mo center on the surface and on the structure of the model. Periodic and cluster calculations employing comparable models of silica give similar results. It is shown that the monooxo Mo(VI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
90
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(101 citation statements)
references
References 68 publications
7
90
0
4
Order By: Relevance
“…These theoretical results are consistent with the Raman studies of Lee and Wachs [48,49]. Handzlik et al [50] studied the structure of monomeric molybdenum oxide species in amorphous silica systems using DFT. The results showed that as long as the local structure of silica could be well four-fold bonding to the surface, the monooxo Mo(VI) species would be more stable than the dioxospecies under dehydration conditions, which are rare.…”
Section: Catalytic Gas-phase Partial Oxidation Of Methane Into Formal...supporting
confidence: 81%
“…These theoretical results are consistent with the Raman studies of Lee and Wachs [48,49]. Handzlik et al [50] studied the structure of monomeric molybdenum oxide species in amorphous silica systems using DFT. The results showed that as long as the local structure of silica could be well four-fold bonding to the surface, the monooxo Mo(VI) species would be more stable than the dioxospecies under dehydration conditions, which are rare.…”
Section: Catalytic Gas-phase Partial Oxidation Of Methane Into Formal...supporting
confidence: 81%
“…S5), was generated (Fig. 9B) [45]. Such a strained configuration resulted in an N-H distance of 1.09 Å in the energetically optimized adsorption complex, hence, the interaction of the ammonia molecule with the silanol group results in a nitrogen atom that is in contact with four H atoms in a distance < 1.1 Å, similar like in an ammonium ion.…”
Section: Theorymentioning
confidence: 96%
“…Density functional theory (DFT) calculations were performed to simulate Lewis and Brønsted acidity of the silica-supported molybdenum oxides by applying cluster models adapted from previous studies [42][43][44][45][46]. The Becke three-parameter hybrid functional with Lee-Yang-Parr correlation functional (B3LYP) together with Ahlrichs' triple-zeta split-valence basis set augmented by polarization functions (def2TZVP or def2TZVPP, respectively) were chosen for the calculations [47,48].…”
Section: Theorymentioning
confidence: 99%
“…Previously, extrinsic defects in MoO 3 crystals such as Na, 47 Li 3,51 and H 52,53 have been studied with DFT, but so far DFT studies of the interaction between MoO 3 and silicon have only examined molybdenum oxides on silica surfaces. [54][55][56] In this paper, the possibility of silicon diffusion in crystalline MoO 3 is investigated and its effect on electronic properties is explored.…”
Section: Introductionmentioning
confidence: 99%